Force-dependent calcium signaling and its pathway of human neutrophils on P-selectin in flow. Issue 2 (18th January 2017) - Huang, Bing; Ling, Yingchen; Lin, Jiangguo; Du, Xin; Fang, Ying; Wu, Jianhua
Abstract: P-selectin engagement of P-selectin glycoprotein ligand-1 (PSGL-1) causes circulating leukocytes to roll on and adhere to the vascular surface, and mediates intracellular calcium flux, a key but unclear event for subsequent arresting firmly at and migrating into the infection or injured tissue. Using a parallel plate flow chamber technique and intracellular calcium ion detector (Fluo-4 AM), the intracellular calcium flux of firmly adhered neutrophils on immobilized P-selectin in the absence of chemokines at various wall shear stresses was investigated here in real time by fluorescence microscopy. The results demonstrated that P-selectin engagement of PSGL-1 induced the intracellular calcium flux of firmly adhered neutrophils in flow, increasing P-selectin concentration enhanced cellular calcium signaling, and, force triggered, enhanced and quickened the cytoplasmic calcium bursting of neutrophils on immobilized P-selectin. This P-selectin-induced calcium signaling should come from intracellular calcium release rather than extracellular calcium influx, and be along the mechano-chemical signal pathway involving the cytoskeleton, moesin and Spleen tyrosine kinase (Syk). These results provide a novel insight into the mechano-chemical regulation mechanism for P-selectin-induced calcium signaling of neutrophils in flow.